Análisis de costos de consumo energético eléctrico en el período 2012-2013.En el proceso de perforación de pozos petroleros en la empresa HELMERICH AND PAYNE del Ecuador para mejorar la gestión energética. Diseño de un plan de gestión energética eléctrica. - León Segovia, Marco Aníbal (2014)
Helmerich and Payne in order to promote energy conservation has been engaged energy efficiency studies; over the time some good practices has been being developed which objective has been the mitigation of negative effects that excessive fossil fuel consumption causes and its impact on the environment, good practices as equipment upgrades and their systems and subsystem, emissions sample test and taking immediately action when values are scattered from the current regulations; however there is much to do to contribute to the decrease in fuel consumptions and optimizing resources to thereby achieve the objectives with the least impact on the environment and society. Consumption rates were measured with indicators of final product that will allow our manager to take best decisions to achieve an efficient use of energy carriers. I determined the main variable that has influence in the energy consumption and using statistic; I determinate specific consumption indicators.